(untitled) (Communications in Computational Physics, 2021)
In this paper, we propose accurate Riemann solvers for detonation and deflagration with sharp interface in high dimension. The standard finite volume scheme is used for each fluid away from material interface, the detonation and the deflagration interfaces are captured by the level set method, small cut cells are treated with a mixing procedure to get stable algorithm. By Riemann solver for the detonation and the deflagration, the interface fluxes are obtained. With the help of the adaptive multi-resolution algorithms, we extend the method to three dimension conveniently. Numerical examples in two or three-dimension are carried out to demonstrate the potential and robustness of the method.